2014
DOI: 10.1073/pnas.1414389111
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of quiescent adult oligodendrocyte precursor cells into malignant glioma through a multistep reactivation process

Abstract: How malignant gliomas arise in a mature brain remains a mystery, hindering the development of preventive and therapeutic interventions. We previously showed that oligodendrocyte precursor cells (OPCs) can be transformed into glioma when mutations are introduced perinatally. However, adult OPCs rarely proliferate compared with their perinatal counterparts. Whether these relatively quiescent cells have the potential to transform is unknown, which is a critical question considering the late onset of human glioma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 84 publications
8
115
2
Order By: Relevance
“…In our previous studies, we found that, upon the introduction of p53/NF1 mutations into neural stem cells, cell lineage-specific analysis revealed a dramatic increase of G/R ratio at pre-malignant stage only in oligodendrocyte precursor cells (OPCs) but not in any other brain cell types (Liu et al, 2011b). Along with other evidences, we pinpointed OPC as the cell-of-origin in this model, a finding supported by other studies (Assanah et al, 2006;Galvao et al, 2014;Lindberg et al, 2009Lindberg et al, , 2014Persson et al, 2010). …”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…In our previous studies, we found that, upon the introduction of p53/NF1 mutations into neural stem cells, cell lineage-specific analysis revealed a dramatic increase of G/R ratio at pre-malignant stage only in oligodendrocyte precursor cells (OPCs) but not in any other brain cell types (Liu et al, 2011b). Along with other evidences, we pinpointed OPC as the cell-of-origin in this model, a finding supported by other studies (Assanah et al, 2006;Galvao et al, 2014;Lindberg et al, 2009Lindberg et al, , 2014Persson et al, 2010). …”
Section: Introductionsupporting
confidence: 86%
“…Our early studies demonstrated that OPCs re-enter cell cycle (reactivation) at 12-day post injection (12 dpi) and subsequently transform into glioma at 180 dpi (Galvao et al, 2014). In this study, we further introduced floxed alleles of mTOR into the tumor model, which harbors p53 and NF1 deletions, to determine the necessity of mTOR in OPC transformation.…”
Section: Deletion Of Mtor Does Not Affect Wt or Pret-opc Proliferationmentioning
confidence: 98%
See 3 more Smart Citations